2017
DOI: 10.1002/cctc.201700047
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodeoxygenation of Phenol over Zirconia‐Supported Catalysts: The Effect of Metal Type on Reaction Mechanism and Catalyst Deactivation

Abstract: This work aims at investigating the effect of the typeo fm etal (Pt, Pd, Rh, Ru, Cu, Ni, Co) on the performanceofZ rO 2 -supported catalystsf or the hydrodeoxygenation of phenol in the gas phase at 573 Ka nd 1atm. Twod ifferent reactionp athways take place depending on the typeo ft he metal. For Pt/ZrO 2 and Pd/ZrO 2 catalysts, phenol is mainly tautomerized,f ollowed by hydrogenation of the C=Cb ond of the tautomer intermediate formed, producing cyclohexanonea nd cyclohexanol.B y contrast, the directd ehydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 55 publications
0
61
0
2
Order By: Relevance
“…Noronha et al. investigated the effect of the type of metal (Pt, Pd, Rh, Ru, Cu, Ni, Co) on the performance of ZrO 2 ‐supported catalysts for phenol hydrodeoxygenation . Pd/ZrO 2 provided the best catalytic activity among the prepared catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Noronha et al. investigated the effect of the type of metal (Pt, Pd, Rh, Ru, Cu, Ni, Co) on the performance of ZrO 2 ‐supported catalysts for phenol hydrodeoxygenation . Pd/ZrO 2 provided the best catalytic activity among the prepared catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Various types of catalysts have been investigated for HDO of phenolics . Among those catalysts, transition metal (such as Pd, Pt and Ru) supported on reducible metal oxides (such as TiO 2 , CeO 2 and ZrO 2 ) have been extensively studied,, since they have shown increased selective deoxygenation to aromatics. The possible reason has been ascribed to the oxiphilic site of reducible oxide favors tautomerization of phenol and, therefore, facilitates the formation of aromatics,, or the metal/support interface site favors direct cleavage of C aromatic ‐OH bond toward aromatics ,.…”
Section: Introductionmentioning
confidence: 99%
“…Among those catalysts, transition metal (such as Pd, Pt and Ru) supported on reducible metal oxides (such as TiO 2 , CeO 2 and ZrO 2 ) have been extensively studied,, since they have shown increased selective deoxygenation to aromatics. The possible reason has been ascribed to the oxiphilic site of reducible oxide favors tautomerization of phenol and, therefore, facilitates the formation of aromatics,, or the metal/support interface site favors direct cleavage of C aromatic ‐OH bond toward aromatics ,. By varying particle sizes of Ru on TiO 2 via changing Ru loadings, Omotoso et al suggested that the perimeter site of Ru‐TiO 2 interface is the active site for deoxygenation of m‐cresol to toluene at 400 °C .…”
Section: Introductionmentioning
confidence: 99%
“…The change in product distribution was explained with the loss of Pd and support interaction due to carbon deposition; metal sintering; and loss of Lewis acid sites on the support. [36] Teles et al [22] also reported deactivation of various metals (Pt, Pd, Rh, Ru, Cu, Ni and Co) on ZrO 2 . The main reasons for deactivation were metal sintering and the decrease of the number of oxophilic sites caused by strong adsorption of reaction intermediates.…”
Section: Characterization and Reusability Of Spent Catalystsmentioning
confidence: 96%
“…Recently, the HDO of phenolics has been studied extensively to produce aromatics with base metal [18][19][20] or noble metal [14,15,[21][22][23][24] catalysts. Cyclohexane and other non-aromatics have also been obtained with base [16,25] and noble [15,22,23,[26][27][28] metal catalysts. Product selectivities and reaction rates can be strongly influenced by the solvent and the phase distribution of the components in the reaction mixture.…”
Section: Introductionmentioning
confidence: 99%